Environmental Application of Telon Blue AGLF Adsorption on Sunflower Pulp: A Response Surface Methodology Approach and Kinetic Study - Ferda Gönen; Esra Köylü (Journal of Chemistry)
The adsorptive removal of Telon Blue AGLF (TB AGLF) from aqueous solution using sunflower pulp was studied. The effects of pH, adsorbent dose, temperature, and initial dye concentration on the adsorption capacity and the removal % of TB AGLF were investigated. Experimental results showed that sunflower pulp was excellent agroindustrial adsorbent with maximum dye removal efficiency of 97.22% for a very short time (under conditions of 100 mg L−1 initial dye concentration, pH = 3, T=50°C, and 1 g L−1 of adsorbent dose). The binary effects of initial dye concentration and temperature on the adsorption properties of sunflower pulp were analysed by RSM and two model equations for predicting adsorption capacity and dye removal % of pulp because arbitrarily chosen initial dye concentration and temperature were developed by using response surface methodology (RSM). Experimental values of the adsorption capacity and dye removal % were in good agreement with the predicted values by the improved models. Adsorption experiments and kinetic regression results indicated that the experimental data were well defined with pseudo-second-order kinetic model.